Global shocks and their impact on the Tanzanian Economy - Fiseha Haile (Kiel Institute for the World Economy (IfW), 2016)
Plummeting commodity prices, China's economic malaise, and global financial market turbulence have recently wreaked havoc on African economies. This paper investigates whether, and to what extent, these intertwined shocks spillover into the Tanzanian economy. The author finds that a 1 percentage point (ppts) drop in China's investment growth is associated with a decline in Tanzania's export growth of roughly 0.60 ppts. A 1 percent fall in commodity prices leads to 0.65 percent lower exports value. The results suggest that a hard landing of the Chinese economy to its 'new normal' would doubtless send shock waves through the Tanzanian economy by further driving down commodity demand and prices as well as lowering development finance. In contrast, financial market volatility has a fairly negligible impact on economic growth. The main results stand up well to a wide-array of robustness checks.
Keywords: C32; F4; O11; 330; China; Tanzania; commodity prices; investment; exports; cointegrated VAR model